The Quality of Service of CV Lestari Jaya - R. Maman Nurochman; Raya Mustiraya,; Lita Juliati Amelia; Arini Permata Sari; Rika Asriyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Research on the quality of grocery sales services, in the initial observation found problems regarding consumer discomfort when buying including incomplete facilities and infrastructure, employee knowledge is still lacking regarding the goods in the store, lack of responsiveness of consumer needs for new products due to limited availability of goods from its distribution center. The purpose of this study was to determine the cause of the low quality of service and to provide efforts to overcome the obstacles that occurred at CV Lestari Jaya. The researcher used the theory of Parasuraman in Tjiptono which consists of five dimensions, namely physical (tangible) reliability, responsiveness, assurance, empathy. The research method used by the author is a descriptive research method with a qualitative approach with data sources from interviews, field observations and documentation. The results of the study showed that the availability of facilities and infrastructure was still lacking, there was no seating provided when consumers were queuing, in terms of employee knowledge they still did not understand what goods were in the store including storage items and were less responsive in terms of the availability of goods in the store regarding new products or goods. So the efforts made are to expand the consumer's space with the employee's space, especially when transacting with the store staff, seating is provided for consumers, and the store owner provides training to his employees regarding the goods in the store, both in terms of price and good service ethics to consumers, and the store first explains to consumers the constraints on the availability of goods from its distribution center, the existence of new products so that they can coordinate first with the warehouse that there is a new product that consumers want, immediately contact the supplier to immediately buy it and send it to the store. Keywords: CV Lestari Jaya, Efforts to overcome obstacles, Service Quality.